ChemInform Abstract: Base‐Catalyzed Intramolecular Hydroamination of Cyclohexa‐2, 5‐dienes: Insights into the Mechanism Through DFT Calculations and Application to the Total Synthesis of epi‐Elwesine. Issue 17 (April 2015) - Rousseau, Geraldine; Lebeuf, Raphael; Schenk, Kurt; Castet, Frederic; Robert, Frederic; Landais, Yannick
Abstract Different pyrrolidine regioisomers are obtained from the intramolecular hydroamination of dienes.